Assessing food security among young farmers in Africa: Evidence from Kenya, Nigeria, and Uganda - Adeyanju, Dolapo; Mburu, John; Gituro, Wainaina; Chumo, Chepchumba; Mignouna, Djana B.; Ogunniyi, Adebayo; Akomolafe, John Kehinde; Ejima, Joseph (Springer, 2023)
Food insecurity remains a serious challenge for many households in Africa and the situation is even more prevalent among young people. However, there is a dearth of empirical evidence on youth food security status in Africa. We assessed the level and determinants of food security among young farmers in Africa. We adopted a multi-stage sampling technique to select 400, 429, and 606 young farmers in Kenya, Nigeria, and Uganda, respectively. Individual food consumption was assessed following a 7 days recall method. The Food Consumption Score, which combines dietary diversity and consumption frequency was used to assess food security status while the determinants of food security were identified using a logistic regression model. Results suggest low dietary diversity across the three countries. Also, the majority of the respondents had an unacceptable food consumption score, suggesting that despite being food producers, young farmers are still food insecure. The odds of being food secure was positively determined by access to extension services, participation in the ENABLE TAAT business incubation programme, and access to market information but, negatively by access to credit, number of employees, Covid-19 pandemic, and location. Additionally, the food security status of young female farmers was positively influenced by age, suggesting that younger youths are less food secure compared to older ones. These results suggest that more efforts should be directed towards improving the food security of young African farmers and that policy- and programme-level interventions should support access to extension services, market information, and land. Additionally, more investments should be directed towards developing need-based agribusiness incubation programmes with an effort to scale existing programmes beyond the regular one-time period.